Upaya Peningkatan Nilai Ekonomi Buah Kelapa di Kalimantan Utara melalui Pemberdayaan Kelompok Masyarakat dalam Pengolahan VCO: Improvement Efforts the Economic Value of Coconut in North Kalimantan through Empowering Community Groups in Processing VCO - Nurjannah, Nurjannah; Cahyaningrum, Widyastuti; Retnaningati, Dewi; Benuk, Vika Dwitami; Ramadhan, Dwi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The processing of coconuts is not yet available in Tarakan City. Coconut production is quite high, but low demand poses a threat to the sustainability of the coconut plantation industry. Therefore, it is necessary to process coconut into products with high benefits and selling value, such as VCO (Virgin Coconut Oil). The processing of coconuts into VCO is relatively simple, making it a straightforward task. Therefore, this activity was carried out in collaboration with the partners of the Nurul Hikmah prayer group, a recitation group consisting of women in RT 5 Juata Kerikil Village, Tarakan, North Kalimantan. In addition to VCO production facilities, partners also need to be equipped with business management, business result analysis, and training related to marketing strategies so that production and sales activities can continue to be carried out continuously after the mentoring activities end. Community group empowerment activities are carried out in several stages, including socialisation, technology application, training, mentoring, and evaluation of activities. The target output of this activity is that partners will be able to apply the proper processing and packaging methods for VCO made from coconut. In addition, partners are also expected to conduct business analysis and effective marketing management. Through the training and mentoring activities conducted, results were obtained in the form of an increase in the understanding and skills of partners in processing and packaging coconuts into VCO. As well as improving the knowledge and ability of partners in conducting business analysis and marketing management needed in VCO's business processes.